(untitled) (Physical Education, Health and Social Sciences, 2025)
The current study was conducted to evaluate the effects of supplemented diets on performance parameters, growth, feeding behavior, Weight Gain (WG), Specific Growth Rate (SGR) and Feed Conversion Ratio (FCR) of budgerigars (Melopsittacus undulatus) in combination or individually at Community College Laboratory in University of Agriculture, Faisalabad, Punjab, Pakistan. For this purpose, a total of twenty budgerigar’s birds were bought from bird’s market in Faisalabad, Punjab, Pakistan and were randomly distributed to the 5 cages, and each page had 4 birds. These birds remained under observation for 180 days in four treatments (T1, T2, T3, and T4) and three supplemented diets. These three supplemented diets of distinct concentrations of protein (120-130g/day), fat (200-250ul of oil in 120-140g/day) and carbohydrate (130-140g/day) were formulated and gave after 24 hours in this experiment. In the current study, statistical analysis was performed to evaluate performance parameters data represented that both in starter phase and finisher phase, carbohydrate and fat supplemented diets showed significant results considered with the significant level at P<0.05 to enhance weight gain, growth and feeding behavior while protein supplemented diet showed non-significant results as compared to the control diet. Based on the results of this experiment, it is concluded that supplementation of carbohydrate and fat alone enhanced and improved the performance of birds. Future studies are needed to determine whether providing alternate foodstuffs to captive parrots can be used as a mean to ameliorate their health, welfare, and reproductive success via diets.